Spatial Distribution and Quality Status of Open Green Spaces and Parks in Calabar Metropolitan Area, Cross River State, Nigeria - Obiefuna, Josiah Nwabueze; Inah, Ebin Okah; Nkong, Maurice Paul; Ekong, Ame Edet (Studia Ecologiae et Bioethicae, 2025)
Urban green areas are often seen in highly developed countries as urban green lungs because of their ability to mediate between man and nature. However, it is not the case in developing countries, where the means of subsistence are considered pivotal and paramount to human existential status. The study examined spatial distribution of open green spaces and parks in the study area and determined differences in their quality. Data for the study were obtained from both primary and secondary sources. A total of 400 copies of the questionnaire were issued to the respondents. Low-level analysis was done using non-parametric statistics, while a hypothesis was tested using Chi-Square parametric/inferential statistics. The result shows that there are significant differences in urban green areas quality at (χ2 =588.680, p<0.05) and accessibility (χ2 = 942.200, p<0.05) in Calabar Metropolis. Further, a Global Positioning System (GPS) device was used to acquire the coordinates of the green spaces and parks in order to delineate them spatially. Geographic Information systems (GIS) infrastructure was used to visualize the spatial distribution of open green spaces and parks in the area. The result is presented in the map output. It was therefore recommended that the destruction of the flora components of the urban green spaces and parks associated with obtaining wood fuel for energy should be discouraged. Finally, the quality of the open green spaces and parks should be improved through the provision of signposts, walkways, tracks, hiking paths, and cycling routes.